IMPROVING CHILDREN'S INDEPENDENCE THROUGH PLAY METHOD IN EARLY CHILDREN AGED 5-6 YEARS AT PAUD MEKAR MANDIRI BEKASI CITY - Annisa Yusria; Rita Intan Anggraeni (Panca Sakti Bekasi : Jurnal Pendidikan dan Bisnis, 2022)
Educationis a very basic thing for human life, one of which is early childhood education. Early childhood education (PAUD) is an educational unit that becomes an educational institution for children aged 0-6 years. Early childhoodis a golden age because at that age everything they hear and see will become a new education. The task of developing children's independence can also be accustomed to doing some fun activities, one of which is playing activities, because the world of children is the world of play.